Paste and geopolymer mortar

JP2026169135APending Publication Date: 2026-10-16KK TOYOTA CHUO KENKYUSHO
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2026010984
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-04-03
Filing Date
2026-01-27
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

【0016】 メタケイ酸塩及びアルカリ剤を含む水溶液に火山灰ガラスのみを添加した場合、縮重合反応が進行せず、ペーストは固化しない。これは、火山灰ガラスは表面が不活性であり、メタケイ酸塩やアルカリ剤と反応しにくいためと考えられる。 これに対し、メタケイ酸塩、アルカリ剤、及び、火山灰ガラスを含むペーストに、さらにアモルファスシリカ成分を含む第2フィラーを添加すると、ペースト中に実質的にCaが含まれない場合であってもペーストが固化し、実用上十分な強度を持つジオポリマーモルタルが得られる。これは、火山灰ガラスとアモルファスシリカ成分を含む第2フィラーとを併用することによって、火山灰ガラスの表面が活性化されたためと考えられる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026169135000001_ABST
    Figure 2026169135000001_ABST
Patent Text Reader

Abstract

To provide a paste that enables the production of a geopolymer mainly composed of volcanic ash glass without substantially using an active filler containing a large amount of Ca, and a geopolymer mortar produced using the paste. [Solution] The paste comprises an active filler, a metasilicate, an alkaline agent, water, and fine aggregate. The active filler comprises a first filler made of volcanic ash glass and a second filler containing amorphous silica components. The first filler has an SiO2 content of 75 mass% to 85 mass%, an Al2O3 content of 8 mass% to 12 mass%, a CaO content of 1.5 mass% or less, and an amorphous component content of 60 mass% or more. The total CaO content of the paste is 1.5 mass% or less. The geopolymer mortar is obtained by solidifying such a paste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a paste and a geopolymer mortar, and more specifically, to a geopolymer mortar using volcanic ash glass as a main raw material, and a paste for producing the same.

Background Art

[0002] "Geopolymer" is a general term for solidified products obtained by a polycondensation reaction between alumina-silica powder (also called "active filler") and an alkaline solution (for example, aqueous NaOH solution, water glass, etc.). "Geopolymer mortar" refers to a solidified product containing a geopolymer and fine aggregate. "Geopolymer concrete" refers to a solidified product containing a geopolymer, fine aggregate, and coarse aggregate.

[0003] Conventionally, cement-based concrete has been used for the construction of infrastructure facilities such as tunnels, bridges, dams, and buildings. Portland cement is widely used as a raw material for mortar and concrete.

[0004] Portland cement is produced with Ca₃SiO₅ as the main phase and calcium carbonate (CaCO₃) as the main raw material. Therefore, Portland cement emits a large amount of carbon dioxide (CO₂) during production. Specifically, when producing 1[t] of Portland cement, approximately 0.77[t] of CO₂ is emitted from the raw materials. In addition, CO₂ is also emitted when generating thermal energy for heating the raw materials. CO₂ equivalent to 4.5% of Japan's total CO₂ emissions and 8% of the world's total CO₂ emissions is emitted by the cement-related industry. Therefore, carbon neutrality (CN) of infrastructure materials is an urgent task.

[0005] In contrast, geopolymers are expected as infrastructure materials that essentially do not emit CO₂. Various proposals have been conventionally made regarding such geopolymers. For example, Patent Document 1 discloses a geopolymer molded article obtained by solidifying a mixture containing volcanic ash, blast furnace granulated slag, water glass, NaOH, water, sand, and polyvinyl alcohol-based fibers. The document states that adding fibers to a geopolymer molded body can improve its strength and toughness.

[0006] Patent Document 2 contains: (a) Hold the sodium silicate solution at 35°C for 5 minutes. (b) Add fly ash to sodium silicate solution to prepare a geopolymer precursor. (c) Fill the mold with the geopolymer precursor, then cure and demold the filler. A geopolymer cured product obtained by this process is disclosed. The document states that preheating a sodium silicate solution at 35°C for at least 5 minutes can delay the start of coagulation of the geopolymer precursor.

[0007] Patent Document 3 discloses a geopolymer obtained by solidifying a mixture containing low-reactivity fly ash, high-reactivity blast furnace slag, an aqueous NaOH solution, and sodium silicate or potassium silicate. The document states that by using a combination of a low-reactivity aluminosilicate binder, such as fly ash, and a high-reactivity aluminosilicate binder, such as blast furnace slag, the viscosity and setting rate of the raw material mixture can be controlled.

[0008] Non-patent document 1 discloses the effects of curing conditions on the compressive strength and reaction mechanism of an alkali-activated material (AAM) that uses volcanic glass powder (VGP) for concrete as a base, with a portion of it replaced by blast furnace slag powder as an active filler. The document states that in order to produce geopolymers using volcanic ash glass, it is necessary to replace 30 mass% of the volcanic ash glass with blast furnace slag.

[0009] In many geopolymers, calcium-containing active fillers such as blast furnace slag and fly ash are often used alone or in combination with other active fillers due to their ease of use. However, blast furnace slag uses CaCO3 as a raw material, and therefore inevitably emits CO2 during its production. Fly ash is coal ash generated during coal-fired power generation, and its production process also emits CO2. Therefore, when geopolymers are manufactured using calcium-containing active fillers such as blast furnace slag and fly ash, complete carbon neutrality (CN) of infrastructure materials cannot be achieved.

[0010] In contrast, volcanic ash glass, while containing small amounts of CaO, is essentially a material that does not emit CO2. Furthermore, if volcanic ash glass can be effectively utilized as a resource, it would be extremely beneficial for volcanic countries like Japan. However, when volcanic ash glass is used alone as the active filler, the raw material mixture does not solidify using conventional methods. In order to solidify the raw material mixture, it was necessary to replace a portion of the volcanic ash glass with blast furnace slag. See Patent Document 1 and Non-Patent Document 1. Furthermore, there are no previous examples of producing a geopolymer with practically sufficient strength from a raw material mixture that contains volcanic ash glass as an active filler and is substantially Ca-free. [Prior art documents] [Patent Documents]

[0011] [Patent Document 1] Japanese Patent Publication No. 2019-116393 [Patent Document 2] Japanese Patent Publication No. 2012-240852 [Patent Document 3] Special Publication No. 2019-521059 [Non-patent literature]

[0012] [Non-Patent Document 1] Ohsako et al., "Influence of Curing Conditions on Strength Development and Reaction Mechanism of Alkali-Activated Materials Based on Volcanic Glass Fine Powder", Proceedings of the Japan Concrete Institute Annual Meeting, 46(2024) 1195 Summary of the Invention Problem to be Solved by the Invention

[0013] The problem to be solved by the present invention is to provide a paste that enables production of a geopolymer using volcanic ash glass as the main raw material without substantially using an active filler containing a large amount of Ca. Further, another problem to be solved by the present invention is to provide a geopolymer mortar produced using such a paste. Means for Solving the Problem

[0014] To solve the above problem, the paste according to the present invention has the following configuration. (1) The paste contains an active filler, a metasilicate, an alkali agent, water, and fine aggregate, The active filler includes a first filler composed of volcanic ash glass and a second filler containing an amorphous silica component. (2) The first filler has an SiO₂ content of 75 mass% or more and 85 mass% or less, an Al₂O₃ content of 8 mass% or more and 12 mass% or less, a CaO content of 1.5 mass% or less, and an amorphous component content of 60 mass% or more. (3) The paste has a total CaO content of 1.5 mass% or less.

[0015] The geopolymer mortar according to the present invention is obtained by solidifying the paste according to the present invention. Effects of the Invention

[0016] When volcanic ash glass alone is added to an aqueous solution containing metasilicate and an alkaline agent, the condensation polymerization reaction does not proceed, and the paste does not solidify. This is thought to be because the surface of volcanic ash glass is inert and does not react easily with metasilicate and alkaline agents. In contrast, when a second filler containing amorphous silica is added to a paste containing metasilicate, an alkaline agent, and volcanic ash glass, the paste solidifies even if it contains substantially no calcium, yielding a geopolymer mortar with sufficient strength for practical use. This is thought to be because the surface of the volcanic ash glass is activated by using it in combination with the second filler containing amorphous silica. [Brief explanation of the drawing]

[0017] [Figure 1] This is the X-ray diffraction pattern of the volcanic ash glass used as the first filler. [Figure 2] This figure shows the relationship between the substitution rate of the second filler and the flexural strength of the geopolymer mortar when NaOH is used as the alkaline agent. [Figure 3] This figure shows the relationship between the substitution rate of metakaolin and the flexural strength of geopolymer mortar when NaHCO3 is used as an alkaline agent. [Figure 4] This figure shows the relationship between the substitution rate of amorphous silica and the flexural strength of geopolymer mortar when NaHCO3 is used as an alkaline agent. [Modes for carrying out the invention]

[0018] [Configuration 1] A paste with the following configuration: (1) The paste comprises an active filler, a metasilicate, an alkaline agent, water, and fine aggregate. The active filler comprises a first filler made of volcanic ash glass and a second filler containing amorphous silica components. (2) The first filler is The SiO2 content is between 75 mass% and 85 mass%. The Al2O3 content is between 8 mass% and 12 mass%. The CaO content is 1.5 mass% or less. The amorphous component content is 60 mass% or more.

[0019] however, The "SiO2 content" of the first filler refers to the ratio of the mass of Si contained in the first filler converted to SiO2 to the total mass of the first filler. The "Al2O3 content" of the first filler refers to the ratio of the mass of Al contained in the first filler, converted to Al2O3, to the total mass of the first filler. The "CaO content" of the first filler refers to the ratio of the mass of Ca contained in the first filler, converted to CaO, to the total mass of the first filler. The "amorphous component content" of the first filler refers to the ratio of the mass of the amorphous component contained in the first filler to the total mass of the first filler.

[0020] (3) The paste has a total CaO content of 1.5 mass% or less. However, the "total CaO content" of the paste refers to the ratio of the mass of Ca contained in the solids other than the fine aggregate, converted to CaO, to the total mass of the solids other than the fine aggregate contained in the paste.

[0021] [Configuration 2] The first filler has an average particle size (D ave The paste described in configuration 1, wherein the particle size is 10 μm or less. However, the above-mentioned "average particle size D ave " refers to the median diameter in the cumulative particle size distribution based on the number of particles, as measured by laser diffraction scattering.

[0022] [Configuration 3] The second filler is a paste according to composition 1 or 2, wherein the CaO content is less than 1.0 mass%. However, the "CaO content" of the second filler refers to the ratio of the mass of Ca contained in the second filler, converted to CaO, to the mass of the second filler.

[0023] [Structure 4] The second filler is a paste according to any one of configurations 1 to 3, comprising amorphous silica and / or metakaolin.

[0024] [Composition 5] The second filler consists of amorphous silica and / or metakaolin. The aforementioned alkaline agent consists of NaOH, The paste according to any one of configurations 1 to 4, wherein the silica equivalent substitution amount of the second filler is 5.0 mass% or more and 30.0 mass% or less. However, the "silica-equivalent substitution amount" of the second filler refers to the ratio of the mass of the amorphous silica component contained in the second filler to the total mass of the active filler.

[0025] [Composition 6] The amount of the aforementioned metasilicate added is 12.0 parts by mass or more and 32.0 parts by mass or less. The amount of alkaline agent added is 3.0 parts by mass or more and 7.0 parts by mass or less. The amount of water added is 50.0 parts by mass or more and 90.0 parts by mass or less. The amount of fine aggregate added is 120.0 parts by mass or more and 360.0 parts by mass or less. Paste as described in Configuration 5.

[0026] However, the "amount added" of the metasilicate, alkaline agent, water, or fine aggregate refers to the mass of the metasilicate, alkaline agent, water, or fine aggregate when the total mass of the activated filler is set to 100.

[0027] [Composition 7] The second filler consists of metakaolin, The aforementioned alkaline agent consists of NaHCO3, The silica equivalent substitution amount of the second filler is 5.0 mass% or more and less than 50.0 mass%. The amount of the aforementioned metasilicate added is 40.0 parts by mass or more and 80.0 parts by mass or less. The amount of alkaline agent added is 7.0 parts by mass or more and 11.0 parts by mass or less. The amount of water added is 40.0 parts by mass or more and 80.0 parts by mass or less. The amount of fine aggregate added is 120.0 parts by mass or more and 360.0 parts by mass or less. Paste the information described in one of the configurations 1 through 4.

[0028] however, The "silica-equivalent substitution amount" of the second filler refers to the ratio of the mass of the amorphous component contained in the second filler to the total mass of the active filler. The "amount added" of the metasilicate, alkaline agent, water, or fine aggregate refers to the mass of the metasilicate, alkaline agent, water, or fine aggregate when the total mass of the activated filler is set to 100.

[0029] [Structure 8] The aforementioned second filler consists of amorphous silica, The aforementioned alkaline agent consists of NaHCO3, The silica equivalent substitution amount of the second filler is 25.0 mass% or more and 60.0 mass% or less. The amount of the aforementioned metasilicate added is 15.0 parts by mass or more and 45.0 parts by mass or less. The amount of alkaline agent added is 3.5 parts by mass or more and 6.0 parts by mass or less. The amount of water added is 30.0 parts by mass or more and 60.0 parts by mass or less. The amount of fine aggregate added is 120.0 parts by mass or more and 360.0 parts by mass or less. Paste the information described in one of the configurations 1 through 4.

[0030] however, The "silica-equivalent substitution amount" of the second filler refers to the ratio of the mass of the amorphous silica component contained in the second filler to the total mass of the active filler. The "amount added" of the metasilicate, alkaline agent, water, or fine aggregate refers to the mass of the metasilicate, alkaline agent, water, or fine aggregate when the total mass of the activated filler is set to 100.

[0031] [Composition 9] A geopolymer mortar obtained by solidifying the paste described in any one of the eight components.

[0032] [Configuration 10] A geopolymer mortar according to composition 9, wherein the four-point bending strength is 5.0 MPa or more. However, the aforementioned "four-point bending strength" refers to the value measured in accordance with JIS R 1601.

[0033] One embodiment of the present invention will be described in detail below. [1. Paste] The paste according to the present invention comprises an active filler, a metasilicate, an alkaline agent, water, and fine aggregate.

[0034] [1.1. Paste Ingredients] [1.1.1. Active Fillers] "Active filler" is one of the main raw materials for forming geopolymers. In conventional geopolymers, various materials containing Si and / or Al were used as active fillers. Specifically, in conventional geopolymers, the active filler was: (a) Fly ash (FA) (coal ash discharged from thermal power plants), (b) Blast furnace slag (BFS) (fine powder obtained by rapidly cooling slag discharged from a blast furnace and crushing the solidified material), (c) Metakaolin (a calcined clay mineral) These were the main terms used.

[0035] In contrast, in the present invention, the active filler comprises a first filler made of volcanic ash glass and a second filler containing amorphous silica components. This is a difference from the conventional invention. The active filler may consist only of the first and second fillers, or it may further include other active fillers (hereinafter also referred to as the "third filler") in addition to these.

[0036] [A. First filler (volcanic ash glass)] The first filler consists of volcanic ash glass. "Volcanic ash glass" refers to a fine powder mainly composed of aluminosilicate glass (volcanic glass) produced by sorting, spheroidizing, and crushing volcanic eruption materials. Volcanic ash glass typically contains SiO2, Al2O3, MgO, Fe2O3, CaO, (Na / K)2O, etc.

[0037] The composition of the first filler (i.e., volcanic ash glass) is not particularly limited, as long as it is capable of producing a geopolymer. The first filler is, in particular, The SiO2 content is between 75 mass% and 85 mass%. The Al2O3 content is between 8 mass% and 12 mass%. The CaO content is 1.5 mass% or less. The amorphous component content is 60 mass% or more. I prefer that. Volcanic ash glass having such a composition is suitable as a first filler material because it solidifies easily even if the paste contains substantially no calcium.

[0038] Here, The "SiO2 content" of the first filler refers to the ratio of the mass of Si contained in the first filler, converted to SiO2, to the total mass of the first filler. The "Al2O3 content" of the first filler refers to the ratio of the mass of Al contained in the first filler, converted to Al2O3, to the total mass of the first filler. The "CaO content" of the first filler refers to the ratio of the mass of Ca contained in the first filler, converted to CaO, to the total mass of the first filler. The "amorphous component content" of the first filler refers to the ratio of the mass of the amorphous component contained in the first filler to the total mass of the first filler. The amorphous component content can be determined by separating the crystalline and amorphous components from the peaks obtained by X-ray powder diffraction (XRD) of the material, for example, using XRD peak analysis software such as JADE (Materials Data).

[0039] Average particle size D of the first filler ave The first filler is D ave The smaller the value, the more readily the first filler reacts with metasilicates and alkaline agents. To obtain high reactivity, the D of the first filler is ave It is preferable that it is 10 μm or less. ave More preferably, the particle size is 8 μm or less, or 6 μm or less. Here, "Average particle size D ave " refers to the median diameter in the cumulative particle size distribution based on the number of particles, as measured by laser diffraction scattering.

[0040] [B. Second Filler] The second filler contains amorphous silica components. The type of second filler is not particularly limited, as long as it contains amorphous silica components. To achieve carbon neutrality (CN) of the infrastructure material, the second filler is preferably made of a material that does not contain a large amount of Ca. Specifically, the second filler is preferably made of a material with a CaO content of less than 1.0 mass%. The CaO content is even more preferably 0.5 mass% or less, or 0.1 mass% or less. Here, the "CaO content" of the second filler refers to the ratio of the mass of Ca contained in the second filler, converted to CaO, to the mass of the second filler.

[0041] Examples of the second filler include amorphous silica, metakaolin, and powdered waste glass. The second filler may consist of one of these, or it may be a mixture containing two or more. The second filler is preferably amorphous silica and / or metakaolin. Both are suitable as second fillers because they have a strong effect in solidifying volcanic ash glass despite being substantially Ca-free.

[0042] [C. Third Filler] The active filler may further include a third filler in addition to the first and second fillers, to the extent that it is possible to produce a geopolymer. Examples of third fillers include Al(OH)3, activated alumina (γ-Al2O3), (SiO2)3·Al2O3, fly ash, blast furnace slag, waste incineration ash, and sewage sludge. To achieve carbon neutrality (CN) in infrastructure materials, the third filler is preferably free of large amounts of CaO. In other words, the active filler is preferably free of fly ash and blast furnace slag.

[0043] [1.1.2. Metasilicate] Metasilicates are components of the alkaline solution used to dissolve the active filler and induce the condensation polymerization and dehydration reaction of silica. In this invention, the type of metasilicate is not particularly limited, as long as it is capable of producing a geopolymer. Examples of metasilicates include sodium metasilicate and potassium metasilicate. The metasilicate may consist of one of these, or it may be a mixture containing two or more.

[0044] Of the metasilicates, sodium metasilicate is particularly preferred. Among metasilicates, sodium metasilicate has a strong effect in solidifying volcanic ash glass. Furthermore, because sodium metasilicate is less expensive than other metasilicates, it can reduce the manufacturing cost of geopolymers. A concentrated aqueous solution of sodium metasilicate is also called "water glass." Furthermore, powdered metasilicates (Na2SiO3·5H2O, Na2SiO3·9H2O) are commercially available. In this invention, one of water glass, Na2SiO3·5H2O, or Na2SiO3·9H2O may be used as the raw material for the metasilicate, or two or more may be used in combination.

[0045] [1.1.3. Alkaline agents] In the present invention, "alkaline agent" refers to alkaline compounds other than metasilicates among the components contained in an alkaline solution used to dissolve the active filler and cause a condensation polymerization and dehydration reaction of silica. In the present invention, the type of alkaline agent is not particularly limited, as long as it is capable of producing a geopolymer. Examples of alkaline agents include sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, and potassium bicarbonate. The alkaline agent may consist of any one of these, or it may be a mixture containing two or more of these. Sodium hydroxide and sodium bicarbonate are particularly preferred as alkaline agents. Among alkaline compounds, sodium hydroxide is highly effective in solidifying volcanic ash glass. Furthermore, sodium bicarbonate is suitable as an alkaline agent because it not only solidifies volcanic ash glass but also has a low environmental impact.

[0046] [1.1.4. Water] Water is an essential component for adjusting the viscosity of the paste to a level suitable for placement. The metasilicate and alkaline agents mentioned above are sometimes commercially available in aqueous solution form. In this case, if the aqueous solution contains a sufficient amount of water to adjust the viscosity of the paste to a level suitable for placement, there is no need to add any more water to the raw material mixture. On the other hand, if the aqueous solution does not contain a sufficient amount of water to adjust the viscosity of the paste to a level suitable for placement, it is preferable to add any more water to the raw material mixture.

[0047] [1.1.5. Fine aggregate] "Fine aggregate" refers to aggregate that passes through a sieve with a mesh size of 10 mm 100% of the time and through a sieve with a mesh size of 5 mm 85% or more of the time. Fine aggregate is a necessary component for increasing the strength of geopolymers. The type of fine aggregate is not particularly limited, as long as it is capable of solidifying the paste.

[0048] [1.1.6. Other ingredients] The paste may contain other ingredients as needed. Other ingredients include, for example, (a) an AE agent for uniformly distributing independent fine air bubbles within the solidified body, (b) A water-reducing agent that adsorbs to the interface of the active filler to increase the fluidity of the slurry. (c) An AE water-reducing agent that has the functions of both an AE agent and a water-reducing agent. (d) A fluidizing agent to increase the fluidity of the paste, (e) A setting retarder that delays the hardening and setting of the paste. (f) Foaming agents for introducing bubbles into the solidified material, (g) Waterproofing agent that eliminates air bubbles in the solidified body and improves watertightness. These are some examples.

[0049] [1.2. Composition of the paste] [1.2.1. Total Ca content] The "total CaO content" of a paste refers to the ratio of the mass of Ca contained in the solids other than the fine aggregate, converted to CaO, to the total mass of the solids other than the fine aggregate contained in the paste.

[0050] When volcanic ash glass is used alone as the active filler, the paste does not solidify. In contrast, as described in Non-Patent Document 1, when 30 mass% of blast furnace slag is added to volcanic ash glass, geopolymers can be produced from the volcanic ash glass. This is thought to be because the volcanic ash glass reacts with the Ca in the blast furnace slag to form calcium silicate hydrate (CSH) or a similar compound. However, since blast furnace slag uses CaCO3 as a raw material, CO2 is inevitably emitted during its production.

[0051] In contrast, the method according to the present invention allows for the solidification of a paste containing volcanic ash glass as the main component, even when using only an activated filler that is substantially free of Ca. To achieve carbon neutrality (CN) in infrastructure materials, the total CaO content is preferably 1.5 mass% or less. More preferably, the total content is 1.0 mass% or less, or 0.5 mass% or less.

[0052] [1.2.2. Silica-equivalent replacement amount of the second filler] The "silica-equivalent substitution amount" of the second filler refers to the ratio of the mass of the amorphous silica component contained in the second filler to the total mass of the active filler. For example, when amorphous silica is used as the second filler, the "mass of the amorphous silica component" is equal to the mass of the amorphous silica itself. On the other hand, when metakaolin is used as a secondary filler, metakaolin contains approximately 50 mass% amorphous silica. Therefore, the "mass of amorphous silica" contained in metakaolin is equal to approximately 50% of the mass of metakaolin.

[0053] Generally, if the silica equivalent replacement amount of the second filler is too low, the paste may become difficult to solidify. On the other hand, the second filler is generally more expensive than volcanic ash glass. Therefore, if the silica equivalent replacement amount of the second filler is excessive, the cost of the paste may increase. Furthermore, if the replacement rate of the second filler is excessive, the strength of the geopolymer mortar may actually decrease. In addition, the optimal value of the silica equivalent replacement amount of the second filler may differ depending on the type of second filler and alkaline agent. Therefore, it is preferable to select the optimal value for the silica equivalent replacement amount of the second filler according to the type of second filler and alkaline agent.

[0054] [A. When the second filler consists of amorphous silica and / or metakaolin, and the alkaline agent consists of NaOH] When the second filler consists of amorphous silica and / or metakaolin, and the alkaline agent consists of NaOH, if the silica-equivalent substitution amount of the second filler is too low, the paste may not solidify easily. Furthermore, even if the paste solidifies, the strength of the solidified paste (geopolymer mortar) may decrease. Therefore, the silica-equivalent substitution amount of the second filler is preferably 5.0 mass% or more. More preferably, the silica-equivalent substitution amount is 6.0 mass% or more, or 7.0 mass% or more. On the other hand, the second filler is generally more expensive than volcanic ash glass. Therefore, if the silica equivalent substitution amount of the second filler is excessive, the cost of the paste may increase. Accordingly, the silica equivalent substitution amount of the second filler is preferably 30.0 mass% or less. More preferably, the silica equivalent substitution amount is 25.0 mass% or less, or 20.0 mass% or less.

[0055] [B. When the second filler consists of metakaolin and the alkaline agent consists of NaHCO3] When the second filler consists of metakaolin and the alkaline agent consists of NaHCO3, if the silica-equivalent substitution amount of the second filler is too low, the paste may not solidify easily. Therefore, the silica-equivalent substitution amount of the second filler is preferably 5.0 mass% or more. More preferably, the silica-equivalent substitution amount is 10.0 mass% or more, or 15.0 mass% or more. On the other hand, if the silica-equivalent substitution amount of the second filler is excessive, the cost of the paste may increase. Therefore, the silica-equivalent substitution amount of the second filler is preferably less than 50.0 mass%. More preferably, the silica-equivalent substitution amount is 45.0 mass% or less, 40.0 mass% or less, 35.0 mass% or less, or 30.0 mass% or less.

[0056] [C. When the second filler consists of amorphous silica and the alkaline agent consists of NaHCO3] When the second filler consists of amorphous silica and the alkaline agent consists of NaHCO3, if the silica-equivalent substitution amount of the second filler is too low, the paste may not solidify easily. Therefore, the silica-equivalent substitution amount of the second filler is preferably 25.0 mass% or more. More preferably, the silica-equivalent substitution amount is 30.0 mass% or more. On the other hand, if the silica-equivalent substitution amount of the second filler is excessive, the paste may become difficult to solidify. Therefore, the silica-equivalent substitution amount of the second filler is preferably 60.0 mass% or less. More preferably, the silica-equivalent substitution amount is 55.0 mass% or less.

[0057] [1.2.3. Amount of metasilicate added] "Amount of metasilicate added" refers to the mass of metasilicate when the total mass of the active filler is set to 100. When using an aqueous solution of a metasilicate, such as water glass, as the metasilicate, "mass of metasilicate" refers to the mass of solids (metasilicates) contained in the water glass.

[0058] Generally, if the amount of metasilicate added is too low, the paste may not solidify properly. On the other hand, if the amount of metasilicate added is too high, the paste may solidify too quickly, making placement difficult. Furthermore, the water resistance of the solidified paste may decrease, and material costs may increase. In addition, the optimal amount of metasilicate added may differ depending on the type of second filler and alkaline agent. Therefore, it is preferable to select the optimal value for the amount of metasilicate added according to the type of second filler and alkaline agent.

[0059] [A. When the second filler consists of amorphous silica and / or metakaolin, and the alkaline agent consists of NaOH] When the second filler consists of amorphous silica and / or metakaolin, and the alkaline agent consists of NaOH, if the amount of metasilicate added is too small, the paste may not solidify easily. Therefore, the amount of metasilicate added is preferably 12.0 parts by mass or more. More preferably, the amount added is 13.0 parts by mass or more, or 14.0 parts by mass or more. On the other hand, if the amount of metasilicate added is excessive, the paste may solidify too quickly, making placement difficult. Furthermore, the water resistance of the solidified paste may decrease, and material costs may increase. Therefore, the amount of metasilicate added is preferably 32.0 parts by mass or less. More preferably, the amount is 30.0 parts by mass or less, or 28.0 parts by mass or less.

[0060] [B. When the second filler consists of metakaolin and the alkaline agent consists of NaHCO3] When the second filler consists of metakaolin and the alkaline agent consists of NaHCO3, if the amount of metasilicate added is too small, the paste may not solidify properly. Therefore, the amount of metasilicate added is preferably 40.0 parts by mass or more. More preferably, the amount added is 45.0 parts by mass or more. On the other hand, if the amount of metasilicate added is excessive, casting becomes difficult, the water resistance of the solidified paste decreases, or material costs may increase. Therefore, the amount of metasilicate added is preferably 80.0 parts by mass or less. More preferably, the amount added is 75.0 parts by mass or less, or 70.0 parts by mass or less.

[0061] [C. When the second filler consists of amorphous silica and the alkaline agent consists of NaHCO3] When the second filler consists of amorphous silica and the alkaline agent consists of NaHCO3, if the amount of metasilicate added is too small, the paste may not solidify easily. Therefore, the amount of metasilicate added is preferably 15.0 parts by mass or more. More preferably, the amount added is 20.0 parts by mass or more. On the other hand, if the amount of metasilicate added is excessive, it may become difficult to pour, the water resistance of the solidified paste may decrease, or the material cost may increase. Therefore, the amount of metasilicate added is preferably 45.0 parts by mass or less. More preferably, the amount added is 40.0 parts by mass or less.

[0062] [1.2.4. Amount of alkaline agent to be added] "Amount of alkaline agent added" refers to the mass of the alkaline agent when the total mass of the active filler is set to 100. When using an aqueous solution of an alkaline compound as an alkaline agent, "mass of the alkaline agent" refers to the mass of the solid content (alkaline compound) contained in the aqueous solution.

[0063] Generally, if the amount of alkaline agent added is too low, the paste may not solidify properly. On the other hand, if the amount of alkaline agent added is too high, the paste may solidify too quickly, making concrete placement difficult. Furthermore, the water resistance of the solidified paste may decrease, and material costs may increase. Moreover, the optimal amount of alkaline agent may differ depending on the type of second filler and alkaline agent. Therefore, it is preferable to select the optimal value for the amount of alkaline agent added according to the type of second filler and alkaline agent.

[0064] [A. When the second filler consists of amorphous silica and / or metakaolin, and the alkaline agent consists of NaOH] When the second filler consists of amorphous silica and / or metakaolin, and the alkaline agent consists of NaOH, if the amount of alkaline agent added is too small, the paste may not solidify easily. Therefore, the amount of alkaline agent added is preferably 3.0 parts by mass or more. More preferably, the amount added is 3.5 parts by mass or more, or 4.0 parts by mass or more. On the other hand, if the amount of alkaline agent added is excessive, the paste may solidify too quickly, making placement difficult. In addition, the water resistance of the solidified paste may decrease, and material costs may increase. Therefore, the amount of alkaline agent added is preferably 7.0 parts by mass or less. More preferably, the amount added is 6.5 parts by mass or less, or 6.0 parts by mass or less.

[0065] [B. When the second filler consists of metakaolin and the alkaline agent consists of NaHCO3] When the second filler consists of metakaolin and the alkaline agent consists of NaHCO3, if the amount of alkaline agent added is too small, the paste may not solidify easily. Therefore, the amount of alkaline agent added is preferably 7.0 parts by mass or more. More preferably, the amount added is 8.0 parts by mass or more. On the other hand, if the amount of alkaline agent added is excessive, it may become difficult to pour, the water resistance of the solidified paste may decrease, or the material cost may increase. Therefore, the amount of alkaline agent added is preferably 11.0 parts by mass or less. More preferably, the amount added is 10.0 parts by mass or less.

[0066] [C. When the second filler consists of amorphous silica and the alkaline agent consists of NaHCO3] When the second filler consists of amorphous silica and the alkaline agent consists of NaHCO3, if the amount of alkaline agent added is too small, the paste may not solidify properly. Therefore, the amount of alkaline agent added is preferably 3.5 parts by mass or more. More preferably, the amount added is 4.0 parts by mass or more. On the other hand, if the amount of alkaline agent added is excessive, it may become difficult to pour, the water resistance of the solidified paste may decrease, or the material cost may increase. Therefore, the amount of alkaline agent added is preferably 6.0 parts by mass or less. More preferably, the amount added is 5.5 parts by mass or less.

[0067] [1.2.5. Amount of water to add] "Amount of water added" refers to the mass of water relative to the total mass of the activated filler, which is set to 100. "Mass of water" refers to the total mass of water contained in the paste. That is, when using an aqueous solution of a metasilicate such as water glass as the metasilicate, and / or when using an aqueous solution of an alkaline compound as the alkaline agent, "mass of water" includes not only the water added to the raw material mixture, but also the water in the aqueous solution.

[0068] Generally, if too little water is added, the viscosity of the paste may become excessively high, making it difficult to apply. On the other hand, if too much water is added, the paste may not solidify properly. Furthermore, the optimal amount of water to add may differ depending on the type of second filler and alkaline agent. Therefore, it is preferable to select the optimal amount of water depending on the type of second filler and alkaline agent.

[0069] [A. When the second filler consists of amorphous silica and / or metakaolin, and the alkaline agent consists of NaOH] When the second filler consists of amorphous silica and / or metakaolin, and the alkaline agent consists of NaOH, if the amount of water added is too small, the viscosity of the paste may become excessively high, making it difficult to apply the paste. Therefore, the amount of water added is preferably 50.0 parts by mass or more. More preferably, the amount added is 55.0 parts by mass or more, or 60.0 parts by mass or more. On the other hand, if too much water is added, the paste may not solidify properly. Therefore, the amount of water added is preferably 90.0 parts by mass or less. More preferably, the amount added is 85.0 parts by mass or less, or 80.0 parts by mass or less.

[0070] [B. When the second filler consists of metakaolin and the alkaline agent consists of NaHCO3] When the second filler consists of metakaolin and the alkaline agent consists of NaHCO3, if the amount of water added is too small, the viscosity of the paste may become excessively high, making it difficult to apply the paste. Therefore, the amount of water added is preferably 40.0 parts by mass or more. More preferably, the amount added is 45.0 parts by mass or more. On the other hand, if too much water is added, the paste may not solidify properly. Therefore, the amount of water added is preferably 80.0 parts by mass or less. More preferably, the amount added is 75.0 parts by mass or less.

[0071] [C. When the second filler consists of amorphous silica and the alkaline agent consists of NaHCO3] When the second filler consists of amorphous silica and the alkaline agent consists of NaHCO3, if the amount of water added is too small, the viscosity of the paste may become excessively high, making it difficult to apply the paste. Therefore, it is preferable to add 30.0 parts by mass or more of water. More preferably, the amount added is 35.0 parts by mass or more. On the other hand, if too much water is added, the paste may not solidify properly. Therefore, the amount of water added is preferably 60.0 parts by mass or less. More preferably, the amount added is 55.0 parts by mass or less.

[0072] [1.2.6. Amount of fine aggregate to be added] "Amount of fine aggregate added" refers to the mass of fine aggregate when the total mass of activated filler is set to 100.

[0073] If the amount of fine aggregate added is too small, the strength of the solidified paste (geopolymer mortar) may decrease. Therefore, the amount of fine aggregate added is preferably 120.0 parts by mass or more. More preferably, the amount added is 150.0 parts by mass or more, or 200.0 parts by mass or more. On the other hand, if the amount of fine aggregate added is excessive, the strength of the solidified product may actually decrease. Therefore, the amount of fine aggregate added is preferably 360.0 parts by mass or less. More preferably, the amount added is 330.0 parts by mass or less, or 300.0 parts by mass or less.

[0074] [2. Geopolymer mortar] The geopolymer mortar according to the present invention is obtained by solidifying the paste according to the present invention.

[0075] [2.1. Paste] The paste contains an active filler, a metasilicate, an alkaline agent, water, and fine aggregate. The active filler also includes a first filler made of volcanic ash glass and a second filler containing amorphous silica components. As details about pasting have been explained above, I will omit further explanation.

[0076] [2.2. Curing conditions] When the paste is filled into a mold and cured under specified temperature and humidity conditions, geopolymer mortar (solidified material) is obtained. The curing conditions are not particularly limited, and the optimal conditions can be selected according to the purpose.

[0077] [2.3. Characteristics: 4-point bending strength] "Four-point bending strength" refers to the value measured in accordance with JIS R 1601.

[0078] Traditionally, when using volcanic ash glass as an active filler, it was said that in order to solidify the paste, it was necessary to use blast furnace slag containing a large amount of Ca as an active filler as well. In contrast, the paste according to the present invention uses volcanic ash glass as an active filler and does not use blast furnace slag, yet it can solidify and produce a geopolymer mortar with sufficient strength for practical use. By optimizing the manufacturing conditions, the four-point bending strength of the geopolymer mortar becomes 5.0 MPa or higher. By further optimizing the manufacturing conditions, the four-point bending strength of the geopolymer mortar becomes 6.0 MPa or higher, 8.0 MPa or higher, or 10.0 MPa or higher.

[0079] Furthermore, it is known that there is a certain correlation between the flexural strength and compressive strength of geopolymer mortar. Specifically, the flexural strength / compressive strength ratio of geopolymer mortar is known to be approximately 1 / 5.5 to 1 / 10. Therefore, for example, a four-point bending strength of 5.0 MPa or higher corresponds to a compressive strength of 27.5 MPa to 50 MPa. Also, a four-point bending strength of 6.0 MPa or higher corresponds to a compressive strength of 33 MPa to 60 MPa.

[0080] [3. Effect] Using activated fillers containing large amounts of Ca, such as blast furnace slag, facilitates the acquisition of high-strength solidified materials (geopolymers). This is because when water is added to Ca-containing activated fillers, the strongly alkaline Ca(OH)2 is produced, which generates fibrous calcium silicate hydrate (CSH) analogues that cause the geopolymer to solidify.

[0081] On the other hand, when only volcanic ash glass is added to an aqueous solution containing metasilicate and an alkaline agent, the condensation polymerization reaction does not proceed, and the paste does not solidify. This is thought to be because the surface of volcanic ash glass is inert and does not react easily with metasilicate and alkaline agents. Conventionally, it was thought that in order to solidify a paste containing volcanic ash glass as an activated filler, it was necessary to use volcanic ash glass in combination with an activated filler containing a large amount of Ca, such as blast furnace slag.

[0082] In contrast, when a second filler containing amorphous silica is added to a paste containing metasilicate, an alkaline agent, and volcanic ash glass, the paste solidifies even if it contains substantially no calcium, yielding a geopolymer mortar with sufficient strength for practical use. This is thought to be because the surface of the volcanic ash glass is activated by using it in combination with the second filler containing amorphous silica. [Examples]

[0083] (Sample No. Al-1 to Al-4, S-1 to S-12, M1 to M8) [1. Raw materials] The following ingredients are used: • Volcanic ash glass (first filler): Manufactured by Silica Japan Co., Ltd., Silica White (registered trademark), amorphous content 60 mass% or more. • Amorphous silica (secondary filler): Manufactured by Admatex Co., Ltd., SO-C5 • Metakaolin (secondary filler): Manufactured by SK Mining Co., Ltd., SK-HMSL, amorphous silica content 52 mass%

[0084] • Al(OH)3 (third filler): Manufactured by Fujifilm Wako Pure Chemical Corporation • γ-Al2O3 (third filler): Manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. • NaAlO2 (third filler): Manufactured by Fujifilm Wako Pure Chemical Corporation

[0085] • Alkaline agent: NaOH 38 mass% aqueous solution • Metasilicate: Aqueous solution prepared by dissolving 138g of water glass (equivalent to JIS Grade 1) in 86g of tap water (34 mass% sodium metasilicate aqueous solution). • Fine aggregate: Manufactured by Marufuji Shoten Co., Ltd., dried silica sand No. 6, produced in Aichi Prefecture. Water: Tap water • Admixture: None

[0086] Figure 1 shows the X-ray diffraction pattern of the volcanic ash glass used as the first filler. Table 1 shows the composition and average particle size D of the volcanic ash glass. ave The specific surface area (SSA) and density (d) are shown.

[0087] [Table 1]

[0088] [2. Preparation of test specimens] The test specimens were prepared using the following procedure. (1) Each raw material was weighed in the specified amount. Refer to Tables 2-4 for the raw material composition of each sample. In all samples, the amount of fine aggregate was 24g. (2) All ingredients except water were placed in a stainless steel beaker and mixed by hand for 1 minute. (3) Add the specified amount of water to the stainless steel beaker and mix by hand for 1 minute.

[0089] (4) The mixed slurry was filled into an acrylic block mold (internal dimensions: 10 x 10 x 50 [mm]). Furthermore, the mold was struck with a plastic hammer to create vibrations and ensure the slurry was packed tightly. (5) A mold filled with slurry was placed in a sealed container with a small amount of water and then sealed. This was placed in a heating furnace heated to 60°C and cured for 20 hours. Because the container was sealed, the curing conditions were 60°C and 100% relative humidity. (6) After curing, the molds were removed and left in the air for one week.

[0090] [3. Test Method] The four-point bending strength of the solidified material was measured in accordance with JIS R 1601 (Room temperature bending test method for fine ceramics).

[0091] [4. Results] The results are shown in Tables 2 to 4. Tables 2 to 4 also show the raw material formulations. "Additional water" refers to water added later to achieve the appropriate viscosity of the raw material mixture. "Quantity" of water glass and alkaline agent refers to the mass of the aqueous solution. "Total water volume" refers to the total amount of water contained in the water glass, alkaline agent, and additional water. Figure 2 shows the relationship between the substitution rate of the second filler and the flexural strength of the geopolymer mortar when NaOH is used as the alkaline agent. The "substitution rate of the second filler" refers to the ratio of the mass of the second filler to the total mass of the active filler. From Tables 2-4 and Figure 2, the following can be seen.

[0092] [4.1. Sample No. Al-1 to Al-4] Table 2 shows the test results for pastes using only volcanic ash glass as the active filler, and pastes using a mixture of volcanic ash glass and an Al-based active filler. None of the samples No. Al-1 to Al-4 solidified.

[0093] [Table 2]

[0094] [4.2. Sample No. S-1~S-12] Table 3 shows the test results of a paste using a mixture of volcanic ash glass and amorphous silica as the active filler. From Table 3, the following can be seen: (1) When a mixture of volcanic ash glass and amorphous silica was used as the active filler, the paste could be solidified by optimizing the composition of the paste. (2) When the composition of the active filler was the same, a tendency was observed for the flexural strength to increase as the content of water glass and alkaline agent increased.

[0095] (3) Sample No. S-1 did not solidify as a slurry. This is thought to be due to the small amount of amorphous silica added. (4) Sample No. S-8 did not solidify as a slurry. This is thought to be due to the small amount of alkaline agent added. (5) When the water glass and alkaline agent content were the same, a tendency was observed for the bending strength to increase as the amorphous silica substitution rate (= silica equivalent substitution amount of amorphous silica) increased. (6) Even when a mixture of volcanic ash glass, amorphous silica, and Al(OH)3 was used as the active filler, the paste solidified. However, a tendency was observed for the flexural strength to decrease as the amount of Al(OH)3 added increased.

[0096] [Table 3]

[0097] [4.3. Sample No. M-1~M-8] Table 4 shows the test results of a paste using a mixture of volcanic ash glass and metakaolin as an active filler. From Table 4, the following can be seen: (1) When a mixture of volcanic ash glass and metakaolin was used as the active filler, the paste could also be solidified. (2) When the composition of the active filler was the same, a tendency was observed for the flexural strength to increase as the content of water glass and alkaline agent increased.

[0098] (3) M-1 and M-2 showed bending strength equivalent to that of S-2 and S-3. Since metakaolin contains approximately 50 mass% amorphous silica, it was found that adding 5.0 mass% or more of amorphous silica relative to the total mass of the active filler allows for the solidification of a paste containing volcanic ash glass. (4) Even when the substitution rate of metakaolin (≒ 2 × silica equivalent substitution amount of metakaolin) was increased, the bending strength did not improve much. This is thought to be because the reactivity between volcanic ash glass and metakaolin is slightly low.

[0099] [Table 4]

[0100] (Sample Nos. M-21~M-27, S-21~S-27) [1. Raw materials] The following ingredients are used: • Volcanic ash glass (first filler): Manufactured by Silica Japan Co., Ltd., Silica White (registered trademark), amorphous content of 60 mass% or more, equivalent to JIS A 6209 Type III. • Amorphous silica (secondary filler): Manufactured by MIT Corporation, RHS E • Metakaolin (secondary filler): Manufactured by SK Mining Co., Ltd., SK-HMSL Metakaolin, amorphous silica content 52 mass%

[0101] • Alkaline agent: NaHCO3 • Metasilicate: Na2SiO3·5H2O(PWG1) • Fine aggregate: Manufactured by Marufuji Shoten Co., Ltd., dried silica sand No. 6, produced in Aichi Prefecture. • Water: Ion-exchanged water • Admixture: None

[0102] [2. Preparation of test specimens] The test specimens were prepared using the following procedure. (1) Each raw material was weighed in the specified amount. Refer to Tables 5-6 for the raw material composition of each sample. In all samples, the amount of fine aggregate was 24g. (2) All ingredients except water were placed in a stainless steel beaker and mixed by hand for 1 minute. (3) Add the specified amount of water to the stainless steel beaker and mix by hand for 1 minute.

[0103] (4) The mixed slurry was poured into an acrylic block mold (internal dimensions: 10 x 10 x 50 [mm]). (5) A mold filled with slurry was placed in a sealed container with a small amount of water and then sealed. This was placed in a heating furnace heated to 60°C and cured for 20 hours. Because the container was sealed, the curing conditions were 60°C and 100% relative humidity. (6) After curing, the molds were removed and left in the air for one week.

[0104] [3. Test Method] The four-point bending strength of the solidified material was measured in accordance with JIS R 1601 (Room temperature bending test method for fine ceramics).

[0105] [4. Results] [4.1. Sample No. M-21~M-27] Table 5 shows the results for samples No. M-21 to M-27, using a mixture of volcanic ash glass and metakaolin as the active filler and NaHCO3 as the alkaline agent. The raw material formulations are also shown in Table 5. Figure 3 shows the relationship between the metakaolin substitution rate and the flexural strength of the geopolymer mortar when NaHCO3 is used as the alkaline agent. From Table 5 and Figure 3, the following can be observed.

[0106] (1) When NaHCO3 was used as the alkaline agent, volcanic ash glass alone did not solidify. See sample No. M-21. (2) When NaHCO3 was used as the alkaline agent and a mixture of volcanic ash glass and metakaolin was used as the active filler, the paste could be solidified regardless of the metakaolin substitution rate (≒2 × the amount of metakaolin replaced in silica equivalent). (3) It was found that even if the substitution rate of metakaolin is around 30-50 mass% (≒ the silica-equivalent substitution rate of metakaolin is around 15-25 mass%), a geopolymer mortar with sufficient bending strength for practical use can be obtained.

[0107] [Table 5]

[0108] [4.2. Sample No. S-21~S-27] Table 6 shows the results for samples No. S-20 to S-26, using a mixture of volcanic ash glass and amorphous silica as the active filler and NaHCO3 as the alkaline agent. The raw material formulations are also shown in Table 6. Figure 4 shows the relationship between the substitution rate of amorphous silica and the flexural strength of the geopolymer mortar when NaHCO3 is used as the alkaline agent. From Table 6 and Figure 4, the following can be observed.

[0109] (1) When NaHCO3 was used as the alkaline agent, volcanic ash glass alone did not solidify. See sample No. S-21. (2) When NaHCO3 was used as the alkaline agent and a mixture of volcanic ash glass and amorphous silica was used as the active filler, the paste could be solidified when the substitution rate of amorphous silica (= silica equivalent substitution amount of amorphous silica) was greater than 20 mass%.

[0110] (3) When the amorphous silica substitution rate exceeded 50 mass%, the strength of the geopolymer mortar decreased. (4) In the combination of amorphous silica and NaHCO3, it was found that a substitution rate of amorphous silica of 25 to 60 mass% is preferable to obtain a geopolymer mortar with sufficient bending strength for practical use. Furthermore, it was found that when the substitution rate of amorphous silica is 30 to 55 mass%, the bending strength becomes 10.0 MPa or higher.

[0111] [Table 6] Although embodiments of the present invention have been described in detail above, the present invention is not limited in any way to the above embodiments, and various modifications are possible without departing from the spirit of the present invention. [Industrial applicability]

[0112] The slurry and geopolymer mortar according to the present invention can be used in the manufacture of infrastructure facilities such as tunnels, bridges, dams, and buildings.

Claims

1. A paste with the following configuration: (1) The paste comprises an active filler, a metasilicate, an alkaline agent, water, and fine aggregate. The active filler comprises a first filler made of volcanic ash glass and a second filler containing amorphous silica components. (2) The first filler is SiO 2 The content is between 75 mass% and 85 mass%, Al 2 O 3 The content is between 8 mass% and 12 mass%, The CaO content is 1.5 mass% or less. The amorphous component content is 60 mass% or more. however, The first filler "SiO 2 "Content" means that the amount of Si contained in the first filler is SiO2 relative to the total mass of the first filler. 2 This refers to the ratio of mass converted to that value. "Al of the first filler 2 O 3 content" refers to the mass ratio of Al contained in the first filler, calculated as Al, relative to the total mass of the first filler 2 O 3 expressed in terms of, The "CaO content" of the first filler refers to the ratio of the mass of Ca contained in the first filler, converted to CaO, to the total mass of the first filler. The "amorphous component content" of the first filler refers to the ratio of the mass of the amorphous component contained in the first filler to the total mass of the first filler. (3) The paste has a total CaO content of 1.5 mass% or less. However, the "total CaO content" of the paste refers to the ratio of the mass of Ca contained in the solids other than the fine aggregate, converted to CaO, to the total mass of the solids other than the fine aggregate contained in the paste.

2. The first filler has an average particle size (D ave The paste according to claim 1, wherein the particle size is 10 μm or less. However, the above-mentioned "average particle size D ave " refers to the median diameter in the cumulative particle size distribution based on the number of particles, as measured by laser diffraction scattering.

3. The paste according to claim 1, wherein the second filler has a CaO content of less than 1.0 mass%. However, the "CaO content" of the second filler refers to the ratio of the mass of Ca contained in the second filler converted to CaO to the mass of the second filler.

4. The paste according to claim 1, wherein the second filler comprises amorphous silica and / or metakaolin.

5. The second filler consists of amorphous silica and / or metakaolin. The aforementioned alkaline agent consists of NaOH, The paste according to claim 1, wherein the silica-equivalent substitution amount of the second filler is 5.0 mass% or more and 30.0 mass% or less. However, the "silica-equivalent substitution amount" of the second filler refers to the ratio of the mass of the amorphous silica component contained in the second filler to the total mass of the active filler.

6. The amount of the metasilicate added is 12.0 parts by mass or more and 32.0 parts by mass or less. The amount of alkaline agent added is 3.0 parts by mass or more and 7.0 parts by mass or less. The amount of water added is 50.0 parts by mass or more and 90.0 parts by mass or less. The amount of fine aggregate added is 120.0 parts by mass or more and 360.0 parts by mass or less. The paste according to claim 5. However, the "amount added" of the metasilicate, alkaline agent, water, or fine aggregate refers to the mass of the metasilicate, alkaline agent, water, or fine aggregate when the total mass of the active filler is set to 100.

7. The second filler consists of metakaolin, The alkaline agent is NaHCO 3 It consists of, The silica equivalent substitution amount of the second filler is 5.0 mass% or more and less than 50.0 mass%, The amount of the metasilicate added is 40.0 parts by mass or more and 80.0 parts by mass or less. The amount of alkaline agent added is 7.0 parts by mass or more and 11.0 parts by mass or less. The amount of water added is 40.0 parts by mass or more and 80.0 parts by mass or less. The amount of fine aggregate added is 120.0 parts by mass or more and 360.0 parts by mass or less. The paste according to claim 1. however, The "silica-equivalent substitution amount" of the second filler refers to the ratio of the mass of the amorphous component contained in the second filler to the total mass of the active filler. The "amount added" of the metasilicate, alkaline agent, water, or fine aggregate refers to the mass of the metasilicate, alkaline agent, water, or fine aggregate when the total mass of the activated filler is set to 100.

8. The aforementioned second filler consists of amorphous silica, The alkaline agent is NaHCO 3 It consists of, The silica equivalent substitution amount of the second filler is 25.0 mass% or more and 60.0 mass% or less. The amount of the metasilicate added is 15.0 parts by mass or more and 45.0 parts by mass or less. The amount of alkaline agent added is 3.5 parts by mass or more and 6.0 parts by mass or less. The amount of water added is 30.0 parts by mass or more and 60.0 parts by mass or less. The amount of fine aggregate added is 120.0 parts by mass or more and 360.0 parts by mass or less. The paste according to claim 1. however, The "silica-equivalent substitution amount" of the second filler refers to the ratio of the mass of the amorphous silica component contained in the second filler to the total mass of the active filler. The "amount added" of the metasilicate, alkaline agent, water, or fine aggregate refers to the mass of the metasilicate, alkaline agent, water, or fine aggregate when the total mass of the activated filler is set to 100.

9. A geopolymer mortar obtained by solidifying the paste described in claim 1.

10. The geopolymer mortar according to claim 9, wherein the four-point bending strength is 5.0 MPa or more. However, the aforementioned "four-point bending strength" refers to the value measured in accordance with JIS R 1601.

Citation Information

Patent Citations

  • Method for producing geopolymer cured body having controlled coagulation start time

    JP2012240852A

  • Geopolymer molding formed from curable composition

    JP2019116393A

  • Pumpable geopolymer compositions for well sealing applications

    JP2019521059A